Penguatan Disiplin positif melalui Pelatihan Guru dalam Implementasi Pembelajaran Kurikulum Merdeka di Sekolah Dasar Negeri Tunggul 2, Kabupaten Sragen - Rasdi, Rasdi; Ningsih, Ayup Suran; Fidiyani, Rini; Hanum, Holy Latifah; Khomariyah, Maulida Nurul; Putri, Fadilla Elza Aida; Wardhani, Harumsari Puspa (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The Merdeka Curriculum has diverse extracurricular learning in which content will be more optimal, giving students enough time to explore concepts and strengthen competencies. Teachers can choose various teaching tools to tailor learning to students’ needs and interests. In conducting teacher learning, of course, teachers encounter multiple characteristics of students. Disciplinary practice is carried out to achieve the learning objectives, but in the observation of the proposal team, many teachers still practice discipline that hurts students. Students feel punished for causing trauma and isolated effects, which, of course, hurts the growth of elementary school students. Teachers of Tunggul 2 Elementary School need an increased understanding of disciplinary patterns based on the Merdeka Curriculum and the school's conditions that require improved infrastructure as a better teaching tool. Positive discipline is interpreted as an act of consciousness and responsibility, as a form of respect for oneself and others around it. The method of service is to provide education through socialization and learning practices.